2016
DOI: 10.1007/s11557-016-1205-9
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts from peat in a tropical peat swamp forest in Thailand and their ability to produce ethanol, indole-3-acetic acid and extracellular enzymes

Abstract: This study aimed to isolate and identify yeasts from peat in To Daeng peat swamp forest in southern of Thailand, and to investigate their ability to produce ethanol from glucose and xylose and to produce indole-3-acetic acid (IAA) and extracellular enzymes. A total of 65 yeast strains were obtained from 15 peat samples using an enrichment technique, and 61 strains were identified to be five species belonging to the phylum Ascomycota, namely Cyberlindnera subsufficiens, Debaryomyces fabryi, Meyerozyma guillierm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 70 publications
3
26
0
Order By: Relevance
“…Similarly, Asian soils were mainly studied as the source of novel yeast species but the information on the distribution of other species is scarce (e.g. Jaiboon, Lertwattanasakul, Limtong, & Limtong, ; Landell et al, ; Limtong, Yongmanitchai, Kawasaki, & Fujiyama, ; Limtong, Yongmanitchai, Tun, Kawasaki, & Seki, ). Forest soils in the Southern Hemisphere are strongly under‐sampled.…”
Section: Properties Of Soils and Diversity Of Soil Typesmentioning
confidence: 99%
“…Similarly, Asian soils were mainly studied as the source of novel yeast species but the information on the distribution of other species is scarce (e.g. Jaiboon, Lertwattanasakul, Limtong, & Limtong, ; Landell et al, ; Limtong, Yongmanitchai, Kawasaki, & Fujiyama, ; Limtong, Yongmanitchai, Tun, Kawasaki, & Seki, ). Forest soils in the Southern Hemisphere are strongly under‐sampled.…”
Section: Properties Of Soils and Diversity Of Soil Typesmentioning
confidence: 99%
“…The organic matter content of the soil samples collected from KK PSF varied considerably in the range of 6.45-93.64%. Therefore, based on the organic matter content as suggested by Huat et al [51], only three samples: S03, S04 and S05, whose organic content was greater than 30%, were considered to be peat soils, whereas, the other samples were soils. The soil samples collected from RBG PSF appeared to contain low amounts of organic matter (2.14-10.51%), therefore, these samples were designated as soils.…”
Section: Physiochemical Characteristic Of Soilsmentioning
confidence: 99%
“…Not only from Thailand but also from tropical regions all over the world, there have been few reports on yeast communities of tropical PSFs. Jaiboon et al [51] reported cultivable yeast species isolated by the enrichment technique from peat at different depths from To Daeng PSF. This forest, which is located in the southern Thailand, is the largest and most fertile primary PSF in the country.…”
Section: Plos Onementioning
confidence: 99%
“…Peat swamp forest (PSF) is a unique ecosystem where peat is formed from the incomplete decomposition of organic matter due to waterlogged conditions [6,7]. This ecosystem is important as it provides global carbon storage for soil organic matter; however, little is known about its microbial diversity [7].…”
mentioning
confidence: 99%
“…Based on their plant communities, tropical PSFs are classified as primary or secondary, with primary PSFs consisting of fertile areas with a high diversity of plant species. Secondary PSFs are primary PSFs that have been compromised by drought, wildfires and human activities, such as logging, land conversion and water drainage for agriculture, resulting in a decrease in the richness of plant species [7,10] studies on yeast diversity in primary and secondary PSFs in Thailand have been carried out recently [6,10], with five novel yeast species, Nakazawaea todaengensis, Saturnispora kantuleensis, Candida kantuleensis, Candida xylosifermentans and Cryptotrichosporon siamense, proposed as a result [11][12][13][14][15].…”
mentioning
confidence: 99%